Sistem informasi tabungan dan manajemen kelompok kurban berbasis responsive web menggunakan metode rapid application development (RAD) - Aryanto, Aryanto; Mulyana, Wide Mulyana (Universitas Muhammadiyah Riau, 2026)
The implementation of the qurban worship is often hampered by the readiness of community cash funds that must be paid in one lump sum close to the day of the event [1]. On the other hand, qurban managers at the mosque level generally still rely on manual recording based on physical books or spreadsheets, which has the potential to trigger recording errors (human error), data loss, and difficulties in mapping participant groupings (pooling) of 7 people per cow [1], [2]. This study aims to design and build a responsive web-based qurban savings information system that facilitates a periodic installment scheme and automates participant grouping [2], [3]. System development was carried out using the Rapid Application Development (RAD) method to accelerate the software engineering cycle through iteration and intensive user feedback [4], [5]. The test results show that the system built using responsive web design successfully makes it easier for the congregation to monitor savings balances and group status transparently through various devices, as well as assisting the committee in managing financial administration and group automation accurately [1], [6], [8].